New data from Jebel Moya and Shaqadud (central Sudan): implications for Late Mesolithic interconnectivity with the Sahara. (15th October 2018) - Brass, Michael; Adam, Ahmed H. A.; Wellings, Joss
Abstract: Building upon Brass' previous research on Jebel Moya, which included a comprehensive reanalysis of the pottery from Wellcome's 1911–14 expeditions curated at the British Museum, new research activities by the University College London–University of Khartoum–NCAM Expedition to the Southern Gezira project have included locating and examining for the first time the Late Mesolithic sherds from Jebel Moya curated at the National Museum in Khartoum. Representative samples from the sites of Shaqadud Midden and Shaqadud S21 at the British Museum have also been re-examined. The aims of these activities were threefold: to test the reliability and cohesiveness of and patterning in the Shaqadud collection through the expanded application of attribute analysis, to determine if Caneva's observations of décor patterns on Jebel Moya's Late Mesolithic sherds could be replicated and to obtain better visibility into the nature of its pottery assemblage from this time, and to use the resulting data to test the viability of the central Sudan being a fulcrum of cultural interchanges during the late sixth and early fifth millennium BC. We conclude that there was a piecemeal establishment of networks along which there was diffusion of ideas and animals, and perhaps low numbers of people, into the central and south-central Sudan. Abstract : بناء على البحوث السابقة التي أجراها مايكل براس حول جبل مویة والذي تضمن إعادة تحلیل شاملة للفخار من بعثات ویلكام 1911–1914 برعایة المتحف البریطاني، وأنشطة بحثیة جدیدة من قبل مشروع البعثة المشتركة لكلیة لندن الجامعیة وجامعة الخرطوم إلى جنوب ولایة الجزیرة، والتي شملت تحدید موقع وفحص، للمرة الأولى، شقف العصر الحجري الوسیط المتأخر من جبل مویة، والمحفوظة في المتحف الوطني بالخرطوم . بالإضافة إلى إعادة فحص عینات تمثیلیة من مواقع وسط شقادود وشقادود S21 الموجودة بالمتحف البریطاني . لھذه الأنشطة ثلاث أھداف : اختبار دقة وتجانس الانماط في مجموعة شقادود من خلال التطبیق الموسع لتحلیل السمات، لتحدید ما إذا كانت ملاحظات كانیفا عن أنماط الزخرفة على شقف العصر الحجري الوسیط المتأخر لجبل مویة یمكن تكرارھا، كذلك الحصول على صورة أفضل عن طبیعة مجموعة الفخار في ھذه الفترة، واستخدام البیانات الناتجة لاختبار قابلیة أن یكون وسط السودان نقطة للتقاطع الثقافي في أواخر الألفیة السادس وأوائل الألفیة الخامسة قبل المیلاد. نستنتج ھنا إلى أنھ كان ھناك إنشاء تدریجي لشبكات انتشرت عبرھا الأفكار والحیوانات، وربما أعداد قلیلة من البشر، إلى وسط وجنوب-وسط السودان .